2015
DOI: 10.1210/jc.2015-1531
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin Reduces Inflammation and Chronic Immune Cell Activation in HIV+ Adults With Impaired Glucose Tolerance

Abstract: Sitagliptin had beneficial systemic and adipose anti-inflammatory effects in cART-treated HIV+ adults with impaired glucose tolerance. Large-scale, long-term studies should determine whether sitagliptin reduces cardiovascular risk and events in HIV+ adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 37 publications
2
16
0
1
Order By: Relevance
“…Another clinical trial showed somewhat similar findings to ours [56]. In HIV-positive glucose intolerant patients, who almost universally have systemic inflammation, sitagliptin significantly decreased plasma IP-10 and sCD14 (a marker of monocyte activation) and AT monocyte chemotactic protein-1 (important in facilitating inflammation) compared to placebo.…”
Section: Plos Onesupporting
confidence: 84%
“…Another clinical trial showed somewhat similar findings to ours [56]. In HIV-positive glucose intolerant patients, who almost universally have systemic inflammation, sitagliptin significantly decreased plasma IP-10 and sCD14 (a marker of monocyte activation) and AT monocyte chemotactic protein-1 (important in facilitating inflammation) compared to placebo.…”
Section: Plos Onesupporting
confidence: 84%
“…Although these results may differ from the reported broad anti-inflammatory effects of other DPP-4 inhibitors in adipose tissue in animals [15,22,23], they appear consistent with limited data on the effect of DPP-4 inhibitors on adipose tissue inflammation in humans [19]. There was a slightly greater decline in adipose tissue abundance of MCP-1 mRNA levels after 8-week sitagliptin treatment compared with placebo in HIV-positive people with impaired glucose tolerance [19]; however, sitagliptin had no effect on the other measured marker of inflammation in that study, EMR-1 [19]. The results of the present study, which include a broad array of inflammatory markers and reflect transcriptional and translational expression of inflammatory proteins as well as inflammation pathway activation, provide more definitive support for a neutral effect of saxagliptin on adipose tissue inflammation in overweight or obese humans at increased risk of Type 2 diabetes.…”
Section: Discussionsupporting
confidence: 73%
“…In preclinical studies, DPP-4 inhibitors reduced trans-endothelial migration and inflammatory cytokine production by T cells in vitro [13,14], and reduced inflammation in both atherosclerotic plaque and adipose tissue in vivo in mice [15,16]. In humans, DPP-4 inhibitors decreased multiple blood pro-inflammatory markers in those with Type 2 diabetes [17,18] and inhibited both systemic and adipose tissue inflammation in HIV-positive people with impaired glucose tolerance [19].…”
Section: Introductionmentioning
confidence: 99%
“…A randomized open label control study showed that the combination of sitagliptin, a dipeptidyl peptidase-4 inhibitor, with ultraviolet phototherapy improved psoriasis more effectively than phototherapy alone 26 . Another observational study reported that sidagliptin decrease inflammation in HIV infection 27 . Also metformin ameriorates disease activity in CIA mice and IBD mice 28 29 .…”
Section: Discussionmentioning
confidence: 99%